Kemampuan Literasi Sains Peserta Didik pada Materi Bentuk-bentuk Energi Melalui E-LKPD Berdiferensiasi dengan Bantuan Wizer.Me - Listyani, Eustakia Frida; Sanita, Yustina Yeyen; Dua Riong, Maria Bernadetha; Wajong, Alfonsus (UNIB Press, 2024)
Science literacy ability is a crusial competency that students must posses in the 21st century to face global challenges. The indicators representing science literacy ability include identifying scientific issues, explaining scientific phenomena, and using scientific evidence. This study aims to describe students’ science literacy abilities through differentiated E-LKPD supported by wizer.me on the topic of forms of energy. The research method employed is qualitative with a descriptive approach. The subjects of the study were 23 students from class X1 at SMAN 1 Waigete. The instruments used include questionnaires to classify students’ learning styles, three essaytest questions to measure students’ science literacy abilities, and open-ended interviews to explore students’ competencies further. The findings revealed that 53.5% of students achieved “very good” in science literacy, 30.43% achieved “good”, and 26.1% fell into “fair” category. The average performance on each indicator was 86.59% for identifying scientific issue, 84.78% for explaning scientific phenomena, and 78.26% for using scientific evidence.